Colonization With Multidrug-Resistant Organisms Among Healthy Adults in the Community Setting: Prevalence, Risk Factors, and Composition of Gut Microbiome - Huang, Yu-Shan; Lai, Liang-Chuan; Chen, Yu-An; Lin, Kuan-Yin; Chou, Yi-Hsuan; Chen, Hsiu-Chi; Wang, Shu-Sheng; Wang, Jann-Tay; Chang, Shan-Chwen (Frontiers in Microbiology, 2020)
Background: The prevalence of colonization with multidrug-resistant organisms (MDROs) among healthy adults in the community is largely unknown. This study investigated the colonization rate of multidrug-resistant Enterobacteriaceae, methicillin-resistant Staphylococcus aureus (MRSA), and vancomycin-resistant enterococci (VRE) in the community in Taiwan, and compared the gut microbiota between MDRO carriers and non-carriers. Methods: This prospective cohort study was conducted from March 2017 to February 2018 at the Hsin-Chu and Jin-Shan branches of National Taiwan University Hospital. Nasal swabs and stool samples were obtained from healthy adults attending a health examination to screen for MDROs. Bacteria isolates of MDROs were tested for antibiotic susceptibility and resistant genes. Relevant data were collected using a standardized questionnaire to evaluate the risk factors for MDROs carriage, and 16S rRNA metagenomics sequencing was performed to analyze gut microbiota. Results: Among 187 participants, 4.6% (8/174) carried MRSA and 41.4% (77/186) carried third-generation cephalosporin-resistant (3GC-R) Escherichia coli or Klebsiella pneumoniae. The carriage rate of AmpC beta-lactamases and ESBL-producing strains were 16.1% and 27.4%, respectively. No carbapenem-resistant Enterobacteriaceae (CRE) or VRE were detected. The dominant resistant gene of E. coli isolates was CTX-M-type (73%), while that of K. pneumoniae was AmpC beta-lactamases (80%). In the multivariate analysis, the significant risk factors for carrying 3GC-R E. coli or K. pneumoniae were being an employee of technology company A (adjusted odds ratio [aOR] 4.127; 95% confidence interval [CI] 1.824–9.336; p=0.001), and traveling to Southeast Asia in the past year (aOR 6.545; 95% CI 1.071–40.001; p=0.042). The gut microbiota analysis showed that the phylum Proteobacteria and the family Enterobacteriaceae were signiﬁcantly more abundant in 3GC-R E. coli and K. pneumoniae carriers. Conclusion: A high rate of Taiwanese adults in the community carried 3GC-R Enterobacteriaceae, while no CRE or VRE colonization was noted. Compared with non-carriers, an expansion of Enterobacteriaceae in gut microbiota was found among 3GC-R Enterobacteriaceae carriers.